Symptoms and Psychological Disorders Associated with Perinatal Losses in Women - Athba Abid Kadhim; Falah Kadhim Khalaf; Hayder Sabah Saleh (Academic Journal of Clinicians, 2025)
Background: One of the main psychological impacts of perinatal losses is the manifestation known as grief . "We call grief the emotional response to the loss of someone or something; each significant loss, each detachment from a significant position, object or loved one provokes a series of reactions or feelings that make us go through a period called mourning". Objective: To assess the symptoms and psychological disorders associated with perinatal losses in women. Patients and method: Cross sectional observational study conducted at our hospital on sample of women shifted from primary health center care. Structured in-depth interviews were conducted with 240 patients who were admitted to the clinic within a year and who presented emotional responses during the medical consultation. Results: Almost 69.2% of the cases presented anxiety-related symptoms, while 47.5% showed sleep disorders and 45.8%, eating disorders. Symptoms related to depression were present in 21.3%; sexual difficulties in 10.4%; attention difficulties in 5%; suicidal ideation in 3.3%; suspicion, somatic problems, phobias, obsessive-compulsive behaviors and aggression in 1.6%, ambivalence in 1.25% and finally, feelings of inadequacy, drug and alcohol problems, inappropriate thinking, self-destructive behaviors, 0.8%, finally 0.4% of the patients with poor impulse control. Conclusion: The most frequent symptomatology was anxiety, followed by sleep disorders, eating disorders and depression to a lesser extent, followed by other types of less recurrent symptoms